Study on The Potency of Methanol Extracts From Xanthosoma nigrum Stellfeld As Natural Anti Oxidant by Thiobarbituric Acid Method - Devi Ratnawati; Lusiana .; Agus Martono; Wahidah Fitriyanti (Aceh International Journal of Science and Technology, 2013)
Abstract- In this research Xanthosoma nigrum Stellfeld (the Purple yam) was selected as experimental material. This plant was collected from Rejang Lebong region, Bengkulu Province. Methanol extract 96% from stem of purple yam was studied its anti-oxidant activity in various concentrations with α-tocopherol (200 ppm) as standard of antioxidant. Antioxidant activity was determined using Thiobarbituric Acid (TBA) method. Linoleic acid was oxidized at 40 ºC for seven days with or without extract and the final product malondialdehyde (MDA) was reacted with thiostembituric acid to be of red colored complex (MDA-TBA) and was then measured by UV-VIS spectrophotometer at λ 532 nm. Stem extract of purple yam with concentration of 100 ppm, 150 ppm, 200 ppm and 300 ppm respectively had the inhibition of 19.32%, 21.85%, 29.47%, and 31.05%.  α-Tocopherol as positive control which showed inhibition ability of 85.14% at 200 ppm. Based on the result obtained in this study, the stem’s extract of Purpel yam plant showed that antioxidant activity was lower than α-tocopherol. Keywords : Xanthosoma nigrum; Stellfeld; MDA; Antioxidant.